Pengaruh Variasi Ketebalan Media Filtrasi Pasir Kuarsa dan Breksi Batu Apung Terhadap Penurunan Kadar Fe dan Kekeruhan Air Sumur Gali - Endah Sumiyaningsih; Tuntas Bagyono; F.X. Amanto Rahardjo (Sanitasi: Jurnal Kesehatan Lingkungan, 2014)
In general, clean water used for daily needs must meet the standards of quality and quantity. In 8 Februari 2013, the measurement of water taken from dug well located at Muhammadiyah Islamic Junior High School in Karangkajen, indicated that the concentration of iron and turbidity exceed-ing the thresholds regulated by MInistry of Health decree No.416 in 1990, so that it need to be processed, one of which is by using filtration medium consists of quartz sand and pumice brec-cia. The study was aimed to identify the influence of the thickness of those medium in reducing concentration of iron and turbidity, by conducting an experiment which followed pre-test post-test with control group design. Data from six replications from three treatment groups and one control group showed that: Filter A (20 cm thicked quartz sand and 60 cm pumice breccia) could reduce iron and turbidity in 83,35 % and 88,99 % respectively; Filter B (30 cm quartz sand 50 cm pumi-ce breccia) reduced iron in 85,52 % and turbidity in 89,81 %; and Filter C (both quartz sand and pumice breccia in 50 cm thickness) could reduce the two parameters in 77,14 % and 88,07 %, respectively; meanwhile in the control group, iron concentration and turbidity were also decreas-ed as much as 76,14 % and 73,18 %. Further statistical analysis with one way anova at 95 % le-vel of significance, concluded that the thickness variation of filtration media affected the reduct-ion of both parameters (p-values: 0,038 and 0,045, respectively). Subsequent analysis with LSD test showed that Filter B had the highest ability.